Transformation of vanadinite [Pb5(VO4)3Cl] by fungi. (29th October 2014) - Ceci, Andrea; Rhee, Young Joon; Kierans, Martin; Hillier, Stephen; Pendlowski, Helen; Gray, Nia; Persiani, Anna Maria; Gadd, Geoffrey Michael
Summary Saprotrophic fungi were investigated for their bioweathering effects on the vanadium‐ and lead‐containing insoluble apatite group mineral, vanadinite [Pb5(VO4)3Cl]. Despite the insolubility of vanadinite, fungi exerted both biochemical and biophysical effects on the mineral including etching, penetration and formation of new biominerals. Lead oxalate was precipitated by Aspergillus niger during bioleaching of natural and synthetic vanadinite. Some calcium oxalate monohydrate (whewellite) was formed with natural vanadinite because of the presence of associated ankerite [Ca(Fe2+, Mg)(CO3)2]. Aspergillus niger also precipitated lead oxalate during growth in the presence of lead carbonate, vanadium(V) oxide and ammonium metavanadate, while abiotic tests confirmed the efficacy of oxalic acid in solubilizing vanadinite and precipitating lead as oxalate. Geochemical modelling confirmed the complexity of vanadium speciation, and the significant effect of oxalate. Oxalate–vanadium complexes markedly reduced the vanadinite stability field, with cationic lead(II) and lead oxalate also occurring. In all treatments and geochemical simulations, no other lead vanadate, or vanadium minerals were detected. This research highlights the importance of oxalate in vanadinite bioweathering and suggests a general fungal transformation of lead‐containing apatite group minerals (e.g. vanadinite, pyromorphite, mimetite) by this mechanism. The findings are also relevant to remedial treatments for lead/vanadium contamination, and novel approaches for vanadium recovery.